THE DIAGNOSIS AND ASSESSMENT OF THE QUALITY OF LIFE IN TINNITUS PATIENTS. A LITERATURE REVIEW - Belanny Dwi Desihartati; Nyilo Purnami (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlight:1. Assessment of the patient’s quality of life is used to establish the diagnosis of tinnitus.2. The assessment is performed using several types of questionnaires: Tinnitus Handicap Inventory (THI), Tinnitus and Hearing Survey (THS), Tinnitus Functional Index (TFI) and Tinnitus Primary Function Questionnaire (TPFQ). 3. THI is the questionnaire that has been translated into Indonesian so that it is easier to use in Indonesia.Background: Tinnitus is a symptom with many different causes that can interfere with daily life. The diagnosis of tinnitus can be carried out, starting by examining the history, physical examination, and audiology, and assessing the quality of life of the patient. Assessment of the patient’s quality of life and the severity of tinnitus was carried out using a questionnaire. Objective: This study aimed to explain the frequency of use of several questionnaires to assess the quality of life of patients with tinnitus, including Tinnitus Handicap Inventory (THI), Tinnitus and Hearing Survey (THS), Tinnitus Functional Index (TFI) and Tinnitus Primary Function Questionnaire (TPFQ). Discussion: The use of THI as a research tool has been recommended for assessing the severity of tinnitus functional, emotional, and catastrophic responses. THS is used as a screening instrument to evaluate tinnitus complaints because of a hearing problem and how frequently it happens. TFI was used for identifying the functional impact on tinnitus patients, to evaluate how tinnitus affects a person’s life, while TPFQ was applied as it is a new questionnaire designed specifically for this objective. Conclusion: Many questionnaires can be used as an assessment of the quality of life of patients with tinnitus. Each questionnaire can be used and has its advantages. THI is a questionnaire that has been translated into Indonesian so that it is easier to assess.